Das Eigene und das Fremde - Einblicke in schulnahe Curriculumarbeit im Bildungsgang Industriekaufmann/-frau zur Konstruktion von interdisziplinärer Verständigung zwischen gewerblich-technischen und kaufmännischen Bildungsgängen. - Koppius, Sebastian Niklas

3D Bézier Guarding: Boundary-Conforming Curved Tetrahedral Meshing - Khanteimouri, Payam; Campen, Marcel (ACM Transactions on Graphics)
We present a method for the generation of higher-order tetrahedral meshes. In contrast to previous methods, the curved tetrahedral elements are guaranteed to be free of degeneracies and inversions while conforming exactly to prescribed piecewise polynomial surfaces, such as domain boundaries or material interfaces. Arbitrary polynomial order is supported. Algorithmically, the polynomial input surfaces are first covered by a single layer of carefully constructed curved elements using a recursive refinement procedure that provably avoids degeneracies and inversions. These tetrahedral elements are designed such that the remaining space is bounded piecewise linearly. In this way, our method effectively reduces the curved meshing problem to the classical problem of linear mesh generation (for the remaining space).

Expansion Cones: A Progressive Volumetric Mapping Framework - Nigolian, Valentin Zénon; Campen, Marcel; Bommes, David (ACM Transactions on Graphics)
Volumetric mapping is a ubiquitous and difficult problem in Geometry Processing and has been the subject of research in numerous and various directions. While several methods show encouraging results, the field still lacks a general approach with guarantees regarding map bijectivity. Through this work, we aim at opening the door to a new family of methods by providing a novel framework based on the concept of progressive expansion. Starting from an initial map of a tetrahedral mesh whose image may contain degeneracies but no inversions, we incrementally adjust vertex images to expand degenerate elements. By restricting movement to so-called expansion cones , it is done in such a way that the number of degenerate elements decreases in a strictly monotonic manner, without ever introducing any inversion. Adaptive local refinement of the mesh is performed to facilitate this process. We describe a prototype algorithm in the realm of this framework for the computation of maps from ball-topology tetrahedral meshes to convex or star-shaped domains. This algorithm is evaluated and compared to state-of-the-art methods, demonstrating its benefits in terms of bijectivity. We also discuss the associated cost in terms of sometimes significant mesh refinement to obtain the necessary degrees of freedom required for establishing a valid mapping. Our conclusions include that while this algorithm is only of limited immediate practical utility due to efficiency concerns, the general framework has the potential to inspire a range of novel methods improving on the efficiency aspect.

Collapsing Embedded Cell Complexes for Safer Hexahedral Meshing - Brückler, Hendrik; Campen, Marcel (ACM Transactions on Graphics)
We present a set of operators to perform modifications, in particular collapses and splits, in volumetric cell complexes which are discretely embedded in a background mesh. Topological integrity and geometric embedding validity are carefully maintained. We apply these operators strategically to volumetric block decompositions, so-called T-meshes or base complexes, in the context of hexahedral mesh generation. This allows circumventing the expensive and unreliable global volumetric remapping step in the versatile meshing pipeline based on 3D integer-grid maps. In essence, we reduce this step to simpler local cube mapping problems, for which reliable solutions are available. As a consequence, the robustness of the mesh generation process is increased, especially when targeting coarse or block-structured hexahedral meshes. We furthermore extend this pipeline to support feature alignment constraints, and systematically respect these throughout, enabling the generation of meshes that align to points, curves, and surfaces of special interest, whether on the boundary or in the interior of the domain.

Galaxy Maps: Localized Foliations for Bijective Volumetric Mapping - Hinderink, Steffen; Campen, Marcel (ACM Transactions on Graphics)
A method is presented to compute volumetric maps and parametrizations of objects over 3D domains. As a key feature, continuity and bijectivity are ensured by construction. Arbitrary objects of ball topology, represented as tetrahedral meshes, are supported. Arbitrary convex as well as star-shaped domains are supported. Full control over the boundary mapping is provided. The method is based on the technique of simplicial foliations, generalized to a broader class of domain shapes and applied adaptively in a novel localized manner. This increases flexibility as well as efficiency over the state of the art, while maintaining reliability in guaranteeing map bijectivity.

HalfedgeCNN for Native and Flexible Deep Learning on Triangle Meshes - Ludwig, Ingmar; Tyson, Daniel; Campen, Marcel (Computer Graphics Forum)
Abstract We describe HalfedgeCNN, a collection of modules to build neural networks that operate on triangle meshes. Taking inspiration from the (edge‐based) MeshCNN, convolution, pooling, and unpooling layers are consistently defined on the basis of halfedges of the mesh, pairs of oppositely oriented virtual instances of each edge. This provides benefits over alternative definitions on the basis of vertices, edges, or faces. Additional interface layers enable support for feature data associated with such mesh entities in input and output as well. Due to being defined natively on mesh entities and their neighborhoods, lossy resampling or interpolation techniques (to enable the application of operators adopted from image domains) do not need to be employed. The operators have various degrees of freedom that can be exploited to adapt to application‐specific needs.

Erklärungsverläufe und -inhalte aus Sicht Erklärender - eine qualitative Studie - Schaffer, Michael; Buhl, Heike M.

Gelingensbedingungen der phasenübergreifenden Zusammenarbeit in der Lehrkräftebildung zur Entwicklung digitalisierungsbezogener Ressourcen in Communities of Practice - Niemann, Jan; Drossel, Kerstin; Eickelmann, Birgit; Raneck-Kuhlmann, Anna; Buhl, Heike M. (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Zuge der digitalen Transformation der Gesellschaft steht die Lehrkräftebildung vor der Herausforderung, (angehenden) Lehrkräften Kompetenzen zu vermitteln, um schulische Lehr-Lernprozesse zeitgemäß zu gestalten. Eine Möglichkeit liegt dabei in der Entwicklung theoretisch fundierter und praxisorientierter digitalisierungsbezogener Ressourcen, die für diese Zwecke genutzt werden können. Um solche Ressourcen zu entwickeln, erscheint der Ansatz der phasenübergreifenden Zusammenarbeit in Communities of Practice (CoPs) der Lehrkräftebildung vielversprechend, da hier die Expertise aller Phasen genutzt werden kann. Bisherige Forschungsergebnisse zu Gelingensbedingungen der Zusammenarbeit lassen auf Faktoren wie Zielorientierung, Aufgabenbewältigung, Zusammenhalt oder Verantwortungsübernahme schließen, beziehen sich jedoch überwiegend auf Teams im Allgemeinen oder CoPs aus dem Wirtschaftskontext. Bisher unerforscht sind damit Gelingensbedingungen für die phasenübergreifende Zusammenarbeit in der Lehrkräftebildung, weshalb der vorliegende Beitrag diese Thematik untersucht. Zur Bearbeitung dieses Forschungsdesiderates werden quantitative und qualitative Daten aus dem COMeIN-Verbundvorhaben (Communities of Practice für eine innovative Lehrkräftebildung in NRW) herangezogen. Mittels einer multiplen Regressionsanalyse wurde die Aufgabenbewältigung in den CoPs als zentraler Prädiktor für positiv wahrgenommene phasenübergreifende Zusammenarbeit identifiziert. Die qualitative Inhaltsanalyse verdeutlicht zudem u.a. die hohe Relevanz der Beachtung der unterschiedlichen Systemlogiken der lehrkräfte-bildenden Phasen. Die Ergebnisse können dazu beitragen, die Zusammenarbeit der lehrkräftebildenden Phasen in CoPs zu verbessern, um so gesellschaftliche Transformationen in der Lehrkräftebildung adäquat mitzugestalten.

Gelingensbedingungen der phasenübergreifenden Zusammenarbeit in der Lehrkräftebildung zur Entwicklung digitalisierungsbezogener Ressourcen in Communities of Practice - Niemann, Jan; Drossel, Kerstin; Eickelmann, Birgit; Raneck-Kuhlmann, Anna; Buhl, Heike M. (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)

Gelingensbedingungen der phasenübergreifenden Zusammenarbeit in der Lehrkräftebildung zur Entwicklung digitalisierungsbezogener Ressourcen in Communities of Practice - Niemann, Jan; Drossel, Kerstin; Eickelmann, Birgit; Raneck-Kuhlmann, Anna; Buhl, Heike M. (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)

A mixed-methods study of the quality of parental support during adolescents' information-related Internet use as a co-construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Security Analysis of the 3MF Data Format - Rossel, Jost; Mladenov, Vladislav; Somorovsky, Juraj (Proceedings of the 26th International Symposium on Research in Attacks, Intrusions and Defenses)
3D printing is a well-established technology with rapidly increasing usage scenarios both in the industry and consumer context. The growing popularity of 3D printing has also attracted security researchers, who have analyzed possibilities for weakening 3D models or stealing intellectual property from 3D models. We extend these important aspects and provide the first comprehensive security analysis of 3D printing data formats. We performed our systematic study on the example of the 3D Manufacturing Format (3MF), which offers a large variety of features that could lead to critical attacks. Based on 3MF’s features, we systematized three attack goals: Data Exfiltration (dex), Denial of Service, and UI Spoofing (uis). We achieve these goals by exploiting the complexity of 3MF, which is based on the Open Packaging Conventions (OPC) format and uses XML to define 3D models. In total, our analysis led to 352 tests. To create and run these tests automatically, we implemented an open-source tool named 3MF Analyzer (tool), which helped us evaluate 20 applications.
Keywords: Data Format Security; 3D Manufacturing Format; 3D Printing; Additive Manufacturing

Eucharistiekatechese in inklusiver Sicht - Reis, Oliver (Partizipativ, prozesshaft, hoffnungsvoll. Katechese der Gegenwart)

Geschlechter - Verhältnisse - Widersprüche. Eine Einleitung - Hoffarth, Britta; Mentzing, Stina; Richter, Susanne (Geschlechter - Verhältnisse - Widersprüche)

Methoden zur Charakterisierung der Bindemechanismen bei geclinchten elektrischen Kontakten - Reschke, Gregor; Kalich, Jan; Füssel, Uwe (Tagung Werkstoffprüfung 2022: Werkstoffe und Bauteile auf dem Prüfstand, Prüftechnik – Kennwertermittlung – Schadensvermeidung)
Das umformtechnische Fügeverfahren Clinchen ermöglicht ein energiearmes Fügen von Blechen und dient traditionell der Übertragung mechanischer Kräfte. Neue Einsatzgebiete erfordern eine elektrische oder thermische Leitfähigkeit, sodass es notwendig ist, das Clinchen entsprechend zu qualifizieren. Es wurden Untersuchungen an Aluminiumverbindungen durchgeführt, welche mit hohen Kurzzeitströmen belastet wurden. Der Einfluss verschiedener Oberflächenvorbehandlungen wurde betrachtet. Als Charakterisierungsmethode für die Bauteile und die geclinchten Fügeverbindungen wird die Messung des elektrischen Widerstandes herangezogen. Die untersuchten Clinchverbindungen sind fähig, die im Fehlerfall auftretenden Kurzzeitströme zu übertragen. Der Oberflächenzustand übt dabei einen signifikanten Einfluss auf die Clinchpunktausbildung und damit auf deren elektrische Eigenschaften aus. Durch Messung des elektrischen Widerstandes vor und nach dem Fügen sowie nach einer Bestromung mit Fehlerströmen, kann das Kontaktverhalten qualifiziert werden.
Keywords: Clinchen; Bindemechanismen; elektrische Eigenschaften; Aluminium; Kurzzeitbestromung

Innovation and Transfer Processes in the German VET System - Daniel-Söltenfuß, Desiree; Breuing, Friederike; Kückmann, Marie-Ann

Trust and awareness in the context of search and rescue missions - Philippi, Martina (SAS23)

Sprachbildung und interkulturelle Kompetenz im Lehramtsstudium. 10 Jahre Projekterfahrung Vielfalt stärken an der Universität und in der Bildungsregion Paderborn

10 Jahre Vielfalt stärken: Gelingensbedingungen für ein erfolgreiches Theorie-Praxis-Projekt - Decker, Claudia; Zierau, Cornelia (Sprachbildung und interkulturelle Kompetenz im Lehramtsstudium. 10 Jahre Projekterfahrung Vielfalt stärken an der Universität Paderborn und in der Bildungsregion Paderborn)